Muhammad Abduh’s scientific views in the Qur’an - Ahmad , N. Amir; Shuriye, Abdi Omar; Ahmad , Faris (Asian Economic and Social Society, 2012)
This paper aims to analyze Shaykh Muhammad ‘Abduh’s scientific interpretation of the Qur’an as presented in his voluminous works such as Tafsir Juz Amma and Tafsir al-Manar. It will investigate the scientific methods he developed and dynamic perspectives he projected in analyzing Qur’anic text which provides the ground for rational and critical understanding of the text relating to the nature of bacteria, light, and some other pertinent issues in scientific debates. The paper discerns key ideas and themes of scientific worldview that ‘Abduh projected and principle methods he crafted in textual analysis which contribute to promulgate rational and analytical understanding of the text.